2013
DOI: 10.2337/dc12-0940
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-α2-Glycoprotein Is Associated With Insulin Resistance in Humans and Is Regulated by Hyperglycemia, Hyperinsulinemia, or Liraglutide Administration

Abstract: OBJECTIVEZinc-α2-glycoprotein (ZAG) has been proposed to play a role in the pathogenesis of insulin resistance. Previous studies in humans and in rodents have produced conflicting results regarding the link between ZAG and insulin resistance. The objective of this study was to examine the relationships between ZAG and insulin resistance in cross-sectional and interventional studies.RESEARCH DESIGN AND METHODSSerum ZAG (determined with ELISA) was compared with various parameters related to insulin resistance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
2
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 25 publications
8
87
2
3
Order By: Relevance
“…Therefore, we speculated that sitagliptin can increase the release of adipocytokines related to increase insulin sensitivity, indirectly confirming that DPP-IV inhibitor improves insulin resistance. Furthermore, these results are also similar to our previous report that liraglutide, a glucagon-like peptide 1 (GLP 1) analogue, treatment for 16 weeks in nT2DM patients leads to a significant increase in circulating ZAG levels (10). Therefore, it might be speculated that increased ZAG levels can be due to a prolonged activation of the GLP-1 receptor or due to inhibition of DPP-IV and thereby higher availability of endogenous GLP-1.…”
Section: European Journal Of Endocrinologysupporting
confidence: 79%
See 3 more Smart Citations
“…Therefore, we speculated that sitagliptin can increase the release of adipocytokines related to increase insulin sensitivity, indirectly confirming that DPP-IV inhibitor improves insulin resistance. Furthermore, these results are also similar to our previous report that liraglutide, a glucagon-like peptide 1 (GLP 1) analogue, treatment for 16 weeks in nT2DM patients leads to a significant increase in circulating ZAG levels (10). Therefore, it might be speculated that increased ZAG levels can be due to a prolonged activation of the GLP-1 receptor or due to inhibition of DPP-IV and thereby higher availability of endogenous GLP-1.…”
Section: European Journal Of Endocrinologysupporting
confidence: 79%
“…Very recently, we have demonstrated that circulating ZAG levels are lower in the patients with impaired glucose tolerance (IGT) and patients with newly diagnosed type 2 diabetes mellitus (nT2DM) than in control subjects. Circulating ZAG levels are also positively correlated with ADI, but inversely with BMI, waist-to-hip ratio (WHR), TG, fasting plasma glucose (FPG), fasting insulin (FIns), HbA1c, and homeostasis model assessment of insulin resistance (HOMA-IR) (10). Since the biological actions of ZAG have not been fully understood, it is important to characterize the effect of anti-diabetic treatment, especially new anti-diabetic agents, on the plasma levels of ZAG in nT2DM patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in agreement with Raiszadeh et al, the present data do not support the notion that IL-6 is present in sweat in detectable levels and we suggest that measurement of IL-6 in sweat is not a valid or reliable measurement of systemic IL-6. Moreover, of 180 proteins identified in sweat, only albumin, zinc α2 glycoprotein, gelsolin, apolipoprotein D and clusterin 1 were present in both sweat and plasma (Raiszadeh et al 2012), indicating that future work aimed at using sweat as a potential vehicle for biomarkers or disease should focus on these proteins, as they have already been linked to a number of diseases and pathological conditions (Ceperuelo-Mallafré et al 2009;Dubois et al 2010;Hassan et al 2008;Mracek et al 2011;Rydén et al 2012;Yang et al 2013). …”
Section: )mentioning
confidence: 99%